Remediation of arsenic from contaminated seawater using manganese spinel ferrite nanoparticles: ecotoxicological evaluation in Mytilus galloprovincialis - Coppola, Francesca (2019)
In the last decade different approaches have been applied for water remediation purposes, including the use of nanoparticles (NPs) to remove metals and metalloids from water. Although studies have been done on the toxic impacts of such NPs, very scarce information is available on the impacts of water after decontamination when discharged into aquatic environments. As such, in the present study we aimed to evaluate the ecotoxicological safety of seawater previously contaminated with arsenic (As) and remediated by using manganese-ferrite (MnFe2O4-NPs) NPs. For this, mussels Mytilus galloprovincialis were exposed for 28 days to different conditions, including clean seawater (control), As (1000 μg L−1) contaminated and remediated (As 70 μg L−1) seawater, water containing MnFe2O4- NPs (50 mg L−1) with and without the presence of As. At the end of exposure, concentrations of As in mussels tissues were quantified and biomarkers related to mussels’ metabolism and oxidative stress status were evaluated. Results revealed that mussels exposed to water contaminated with As and to As + NPs accumulated significantly more As (between 62% and 76% more) than those exposed to remediated seawater. Regarding biomarkers, our findings demonstrated that in comparison to remediated seawater (conditions a, b, c) mussels exposed to contaminated seawater (conditions A, B, C) presented significantly lower metabolic activity, lower expenditure of energy reserves, activation of antioxidant and biotransformation defences, higher lipids and protein damages and greater AChE inhibition. Furthermore, organisms exposed to As, NPs or As + NPs revealed similar biochemical effects, both before and after water decontamination. In conclusion, the present study suggests that seawater previously contaminated with As and remediated by MnFe2O4-NPs presented significantly lower toxicity than As contaminated water, evidencing the potential use of these NPs to remediate seawater contaminated with As and its safety towards marine systems after discharges to these environments.